Günter Umberg : Body of Painting mit Bildern aus Kölner Sammlungen. - Poetter, Jochen; Umberg, Günter; Museum Ludwig, Köln (Ostfildern-Ruit : Hatje Cantz Verlag, 2000)
Warhol, Andy ; Flavin, Dan ; Polke, Sigmar ; Kelly, Ellsworth ; Baer, Jo ; Hofmann, Hans ; Johns, Jasper ; Manzoni, Piero ; Trockel, Rosemarie ; Stockholder, Jessica ; Wesley, John ; Federle, Helmut ; Richter, Gerhard ; Calame, Ingrid ; Frize, Bernard ; Klein, Yves ; Kokoschka, Oskar ; Ryman, Robert ; Reed, David ; Artschwager, Richard
Günter Umberg : Body of Painting mit Bildern aus Kölner Sammlungen, Museum Ludwig, Köln, 21.07 - 17.09.2000
boek
Keywords: Umberg, Günter